2016
DOI: 10.3168/jds.2016-11410
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing amounts of milk replacer powder added to whole milk on passage rate, nutrient digestibility, ruminal development, and body composition in dairy calves

Abstract: The aim of this study was to evaluate the effects on feed intake, calf performance, feed efficiency, fecal score, passage rate, apparent nutrient digestibility, development of rumen and other organs, and body composition of increasing the total solids content of liquid feed (whole milk) by adding increasing amounts of milk replacer powder during the preweaning period. Crossbred Holstein-Gyr calves (n=32) were assigned to 1 of 4 treatments (n=8 per group), which consisted of different total solids concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(72 reference statements)
8
8
0
Order By: Relevance
“…The study was not, however, designed to detect differences in growth or diarrhea incidence. Results for fecal DM are consistent with previous findings of Azevedo et al (2016), in which hypertonic CMR (up to 533 mOsm/ kg) did not affect fecal scores.…”
Section: Discussionsupporting
confidence: 90%
“…The study was not, however, designed to detect differences in growth or diarrhea incidence. Results for fecal DM are consistent with previous findings of Azevedo et al (2016), in which hypertonic CMR (up to 533 mOsm/ kg) did not affect fecal scores.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, all animals were evaluated at the same age and we found no difference in BW and ADG in the studied periods, which may justify the absence of differences in mammary fat pad among groups. These results, combined with those observed by Azevedo et al (2016b), who reported no change in the percentage of fat in the body composition of male dairy calves receiving liquid feed with TS concentrations similar to that used in the present study, support the hypothesis of a similar effect on body composition and mammary gland of heifers.…”
Section: Mammary Glandsupporting
confidence: 92%
“…Total DM and water intake up to 240 d of age were similar among treatments and increased with age (P ≤ 0.01; Table 2). Azevedo et al (2016b) demonstrated that male calves receiving liquid feed with the same levels of TS evaluated in the present study did not present differences in ruminal development, indicating similarity between the digestive and absorptive capacities of the animals. These results suggest that the provision of liquid feed with greater TS concentration during the preweaning period did not affect rumen development, therefore not compromising postweaning feed intake.…”
Section: Intake Performance and Growth Measurementssupporting
confidence: 64%
“…Ruminal passage kinetics (Azevedo et al, 2016), nutrient digestion, and VFA absorption (Conrad et al, 1956;Sutton et al, 1963;Khouri, 1969) are difficult to assess in young dairy calves. Overcoming technical complications related to assessment of ruminal passage kinetics, nutrient digestion, and VFA absorption are therefore essential steps toward improving our understanding of dairy calf nutrition.…”
Section: Technical Notementioning
confidence: 99%